Portable Spirometer for Measuring Lung Function Health (FVC and FEV1) - lia andriani; Priyambada Cahya Nugraha; Sari Lutfiah (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
Extreme climate change and air pollution caused by dust, smoke, vehicle exhaust gases and industry can increase the chances of contracting various infectious diseases caused by viruses, especially respiratory infections. Lung volume measurements obtained from air that is inhaled and exhaled by someone can help doctors diagnose abnormalities in the lungs. The purpose of this study was to develop an affordable pulmonary function measurement system, which is a spirometer. The main board consists of a non-inverting amplifier, Arduino microcontroller, LCD and SD Card memory. FVC and FEV1 volume measurements are carried out when the breath blew through the MPX5100DP gas pressure sensor. The sensor’s output is a voltage, which is converted to a volume unit using the venturimeter method. The SD card memory is used to store data. The results of measurement data on respondents with a spirometer comparison device then there is an FVC error of 0.98% 5, FEV1 3.83% and FEVI / FVC 2.50%. This value is still below the error tolerance limit of 5%. The design of this spirometer is portable and low cost to be made for mass production to help people to measure the health of lung function in humans.